Assessment of the serotonin pathway as a therapeutic target for pulmonary hypertension. (24th September 2013) - Gray, Emily A.; Tsuchimochi, Hirotsugu; Pearson, James T.; Sonobe, Takashi; Fujii, Yutaka; Yoshimoto, Misa; Umetani, Keiji; Shirai, Mikiyasu; Schwenke, Daryl O.
Abstract : Blockade of the serotonin reuptake transporter (5‐HTT), using fluoxetine, has been identified as a potential therapeutic target for preventing and, importantly, reversing pulmonary hypertension (PH). This study utilized synchrotron radiation microangiography to determine whether fluoxetine could prevent or reverse endothelial dysfunction and vessel rarefaction, which underpin PH. PH was induced by a single injection of monocrotaline (MCT; 60 mg kg −1 ). Following MCT administration, rats received daily injections of either saline or fluoxetine (MCT+Fluox; 10 mg kg −1 ) for three weeks. A third group of rats also received the fluoxetine regime, but only three weeks after MCT (MCT+FluoxDelay ). Control rats received daily injections of saline. Pulmonary microangiography was performed to assess vessel branching density and visualize dynamic changes in vessel diameter following (i) acute fluoxetine or (ii) acetylcholine, sodium nitroprusside, BQ‐123 (ET‐1A receptor blocker) and L‐NAME (NOS inhibitor). Monocrotaline induced PH that was inevitably terminal. `Delayed' treatment of fluoxetine (MCT+FluoxDelay ) was unable to reverse the progression of PH. Early fluoxetine treatment pre‐PH ( i.e. MCT+Fluox) attenuated but did not completely prevent vascular remodeling, vessel rarefaction and an increase in pulmonary pressure, and it did not prevent pulmonary endothelial dysfunction. Interestingly, fluoxetine treatment did counter‐intuitively prevent the onset of right ventricular hypertrophy. Using synchrotron radiation microangiography, selective blockade of the serotonin reuptake transporter alone is highlighted as not being sufficient to prevent pulmonary endothelial dysfunction, which is the primary instigator for the inevitable onset of vascular remodeling and vessel rarefaction. Accordingly, potential therapeutic strategies should aim to target multiple pathways to ensure an optimal outcome.